Allocation of transmission losses to determine tariff - Adebayo, Adeyinka Victor (Department of Electrical Engineering, 2019)
The recent widespread restructuring and unbundling of the electricity industry has introduced some changes in the organization of the sector, thereby creating a more competitive environment in which each participant must bear its own cost and be responsible for its own contribution to losses in the system. The allocation of transmission losses has become an important issue as this determines how and what to charge each of the participants in the industry. This allocation is best assessed and based on their individual contributions to grid losses. Earlier methods used in loss allocation include: The Pro rata approach which arbitrarily allocates 50% each to the load and generator; the Marginal procedure allocation, which is either positive or negative; the Proportional sharing method which bases its allocation on the Kirchhoff’s current law and allocates no losses to the transmission line and the Equilateral bilateral exchange (EBE) method. Most of the other methods, such as the Game theory method, Circuit theory method, Graph theory method, and Optimization methods are either mathematically complex in operation or time-consuming. And till date, none of these methods could be used to allocate transmission losses with fairness and transparency. Currently, power loss measurements have been estimated based on ideal conditions in which there exist a balanced load and reactive power, while the inefficiency caused by distortion and the unbalanced load is not usually taken into consideration. This research introduces a novel and a fairer method of determining power losses by using the Thévenin impedance in calculating the line parameters used in the determination of power losses. Since losses associated with a transmission power line depend on the wire resistance and the line current (I2 R), the Thévenin equivalent of the system is calculated from the point of connecting each participant (generator or load), i.e. the point of common coupling, to determine the system losses without prior knowledge of the power system supply quantities. This thesis identifies the avoidable losses in the system, which participants pay for because of the inadequacy of current methods which use only reactive powers (inductive and capacitive) to determine the power losses in the allocation of losses and in the calculation of the power system tariff. This report elucidates how to estimate the losses that can be avoided by the participants. This loss is equal to the numerical power difference in the conventional power loss and the new power loss calculation method which utilizes the general power theory where two components that are orthogonal to each other, making non-active power (reactive power and distortion power) are used. This difference, which is an extra loss created by the participants, can be conserved to reduce power generation cost and tariffs. This method which was tested on a standard IEEE test system is transparent, fair and requires a comparatively short time to execute, making it suitable for decision making thus emphasizing the importance of the proposed solution.